Ca2+ signals in astrocytes facilitate spread of epileptiform activity - Heuser, Kjell; Nome, Cecilie G.; Pettersen, Klas H.; Åbjørsbråten, Knut S.; Jensen, Vidar; Tang, Wannan; Sprengel, Rolf; Taubøll, Erik; Nagelhus, Erlend A.; Enger, Rune (Cerebral cortex, 2018)
Abstract. Epileptic seizures are associated with increased astrocytic Ca2+ signaling, but the fine spatiotemporal kinetics of the ictal astrocyte-neuron interp